2019
DOI: 10.21977/d915144538
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Supports to Elementary Teacher Education: Case Study of Preservice Teachers’ Perspectives on Arts Integration

Abstract: This case study investigates the factors that challenge and support preservice teachers' (PST) arts integration beliefs and practices. The participants include a total of 74 PSTs enrolled in a mandatory university arts course at a large Southern university across three consecutive semesters. Concurrent with arts class enrollment, PSTs are also enrolled in their capstone, semester-long, student teaching experience. The authors used PSTs' end-of-semester reflections and the primary data source. Findings illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(41 reference statements)
0
6
0
1
Order By: Relevance
“…Adicionalmente, como han demostrado algunos estudios (p.e., Hipp & Sulentic, 2019), estas actividades transforman las percepciones de los maestros sobre los recién llegados al poner énfasis en su fortaleza y en su capacidad de recuperación, sin negar sus vulnerabilidades, lo que contribuye al desarrollo de la sensibilidad intercultural.…”
Section: Proyecto: "Leila Alaoui Y Los Invisibles"unclassified
“…Adicionalmente, como han demostrado algunos estudios (p.e., Hipp & Sulentic, 2019), estas actividades transforman las percepciones de los maestros sobre los recién llegados al poner énfasis en su fortaleza y en su capacidad de recuperación, sin negar sus vulnerabilidades, lo que contribuye al desarrollo de la sensibilidad intercultural.…”
Section: Proyecto: "Leila Alaoui Y Los Invisibles"unclassified
“…Each of the Art forms have unique histories, language and approaches. Any discussion of the possibility of integrating the Arts with themselves or more particularly with other subject areas has traditionally been problematic because of fears that it will take time away from high-stakes testing, (Lingard et al, 2016 ; Moss et al, 2019 ), the lack of teacher self-efficacy with arts integration (Battersby & Cave, 2014 ; Burnaford et al, 2011 ) and limited teacher professional development (Hipp & Sulentic Dowell, 2019 ; O’Toole, 2018 ). Davis ( 2008 ) and O’Toole ( 2018 ) both argue that arts educators are also concerned that the integration of the Arts with other subjects will obscure the view of the Arts as unique disciplines: Every teacher of an art form has had their subject traduced into menial service as a handmaiden for another subject or even art form – music reduced to rhythm games for maths, visual arts co-opted into painting the sets for the school musical, drama diminished into little skits for history or school camp, media arts turned into critical literacy exercises in English, dance merely a back alley in physical education, and in primary schools all of them lumped together into an amorphous and ill-defined form of Friday afternoon relief called Expressive Arts.…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…She further argued that “deep learning and understanding is more likely when integration is carefully planned to reflect real-world learning experiences” (Ewing, 2020 , p. 78). There is a plethora of evidence that arts integration supports active learning and engagement and deeper, more sustained learning (Burnaford et al, 2011 ; Goldberg, 2021 ; Hipp & Sulentic Dowell, 2019 ). However, as Marshall ( 2014 , p. 105) argues, arts educators need to “fully delineate and promote art integration as the complex, dynamic practice it is so that those outside the field can see its potential”.…”
Section: Contextual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…More elementary classroom teachers might be apt to infuse music into their classrooms when additional opportunities are provided for learning this process (Hipp & Sulentic, 2019; Miksza & Gault, 2014). Byo (1999) found that Florida elementary classroom teachers requested more time to collaborate with elementary general music teachers to better understand national and state music standards.…”
mentioning
confidence: 99%